Cloud and Services Testing Applied in Manufacturing - Alves, F.; Coutinho, C.; Peña-Ortiz, R.; Xu, X; Nieto, A.; Ahola, J.; Saari, L.; Katasonov, A. (Enterprise Interoperability VII: Proceedings of the 8th International Conference on Interoperability for Enterprise Systems and Applications (I-ESA 2016), 2016)
Software testing is a complex and thorough process, which verifies software correctness from bare simple code units to the intricate complexity of fully integrated systems. Such major development contributor element should be planned from the beginning of the project (perhaps even before the code itself), and should play a role as important as the development itself. The use of the latest, fit, and most complete tools is important to ease the testing activities, but in most cases the selection of the best tool is specific to each particular development environment. This article presents an overview of the state-of-the-art in testing methodologies and tools, particularising the use of such tools in the context of the H2020 European project C2NET, which handles, among others, Cloud environments and Web Services.